Between Conventional Narrative and Artistic Experimentation: An Autoethnographic Reflection at the Bandung Festival - Muhammad Qawiem, Hamizan; Muhammad Azri, Ali; Ahmad Kamal Basyah, Sallehuddin (2025)
This article presents an autoethnographic reflection on the creative process and performance experience of a Malaysian theatre production staged at an experimental arts festival in Bandung, Indonesia. The work was rooted in a conventional narrative structure, contrasting with the prevailing performances at the festival, which were predominantly experimental and abstract. This divergence created a space for both tension and learning, as the artist negotiated the intersection between narrative clarity and avant-garde artistic approaches.